Plan de mejoramiento en la calidad de atención y servicio al cliente en la empresa Cintandina S.A. en la ciudad de Cali (2013)
In this research project provides a general description of the current situation Cintandina Company, which for over 50 years has focused its work in terms of research and development in the production and marketing of products and packaging tapes, in order to meet the needs of customers. The central theme of the project is the implementation of an improvement plan that would strengthen the care and service provided by the company. Then, taking into account the situation of the company, it raises a number of strategies for proper implementation of the plan. In turn by developing this new implementation within the company, is to establish a corporate culture that encourages and motivates performance on quality of care and customer service. A fundamental aspect in the development of the project is the creation of a Department of care and customer service, which will charge monitoring, coordination and monitoring of the activities proposed in the plan and subsequent implementation in the company.